Dominant-Negative Regulation of Cell Surface Expression by a Pentapeptide Motif at the Extreme COOH Terminus of an Slo1 Calcium-Activated Potassium Channel Splice Variant - Chiu, Yu-Hsin (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Large-conductance Ca(2+)-activated K(+) (BK(Ca)) channels regulate the physiology of many cell types. A single vertebrate gene variously known as Slo1, KCa1.1, or KCNMA1 encodes the pore-forming subunits of BK(Ca) channel but is expressed in a potentially very large number of alternative splice variants. Two splice variants of Slo1, Slo1(VEDEC) and Slo1(QEERL), which differ at the extreme COOH terminus, show markedly different steady-state expression levels on the cell surface. Here we show that Slo1(VEDEC) and Slo1(QEERL) can reciprocally coimmunoprecipitate, indicating that they form heteromeric complexes. Moreover, coexpression of even small amounts of Slo1(VEDEC) markedly reduces surface expression of Slo1(QEERL) and total Slo1 as indicated by cell-surface biotinylation assays. The effects of Slo1(VEDEC) on steady-state surface expression can be attributed primarily to the last five residues of the protein based on surface expression of motif-swapped constructs of Slo1 in human embryonic kidney (HEK) 293T cells. In addition, the presence of the VEDEC motif at the COOH terminus of Slo1 channels is sufficient to confer a dominant-negative effect on cell surface expression of itself or other types of Slo1 subunits. Treating cells with short peptides containing the VEDEC motif increased surface expression of Slo1(VEDEC) channels transiently expressed in HEK293T cells and increased current through endogenous BK(Ca) channels in mouse podocytes. Slo1(VEDEC) and Slo1(QEERL) channels are removed from the HEK293T cell surface with similar kinetics and to a similar extent, which suggests that the inhibitory effect of the VEDEC motif is exerted primarily on forward trafficking into the plasma membrane.